Planning For the Use of Electronic Access Cards at the Joint Lecture Building Tanjungpura University - Iqram, Andi Muhammad; Junaidi, Junaidi; Husin, Fitriah (Faculty of Engineering, Universitas Tanjungpura, 2024)
Electricity is one of the important energy needs and takes a role in human activities, especially in the Untan Joint Lecture Building, it is very wasteful in terms of electricity usage, we can see from electricity payments in 2022 in May amounting to Rp. 20,111,463, to May 2023 amounting to Rp. 27,504,057. Apart from that lectures at the Tanjungpura University Joint Lecture Building, several inappropriate electrical energy use behaviors were also found. Among them are the use of lighting during the day, air conditioning is turned on when the learning is empty, room facilities are lit when the room is not used and others. As a result, the allocation of high electricity costs in the Untan Joint Lecture Building. To avoid this problem, it is necessary to plan the use of electronic access cards in the Untan Joint Lecture Building. This electronic access card is a tool that functions to cut off or connect electricity to an area or room. So this planning is carried out so that it will provide insight into how to overcome these problems. In this planning, several calculations are carried out, namely total load, energy consumption, energy savings, electrical energy costs, and payback period at the Tanjungpura University Joint Lecture Building. From the results of the calculation of the effect can be seen after the installation of electronic access cards, which can produce large savings, with energy consumption costs after savings in Building A for a month amounting to Rp. 4,203,147,667. And the period needed to cover investment expenditures is the longest for 4 months and the fastest is less than 1 month.